A Review of the Historical Perspectives of Contagious Bovine Pleuropneumonia in Africa and Entry into Nigeria (NTU Journal of Agriculture and Veterinary Science, 2025)
CBPP is a highly contagious and economically significant respiratory disease of cattle. A systematic search of databases from 1987 to 2024 was conducted. This review assesses the history of CBPP in Africa. CBPP is caused by Mycoplasma mycoides subsp. mycoides. The disease’s spread across the African continent has been facilitated by factors such as colonial trade routes, cattle movements, nomadic pastoralism, and environmental conditions. The introduction of CBPP into Nigeria marked a pivotal moment in the country’s agricultural history. This review traces the early documentation of CBPP outbreaks, highlighting the disease’s influence on traditional cattle-rearing practices and the subsequent social and economic consequences. It further examines the role of vaccination efforts, disease monitoring, and government policies in controlling the disease. In Nigeria, CBPP has disrupted cattle herd compositions and cattle movement patterns, with financial costs incurred. This review underscores the importance of continued research as a way out of CBPP.